ВЕКТОР РОЗВИТКУ МЕДИЧНОГО СТРАХУВАННЯ У КОНТЕКСТІ СУЧАСНОЇ МЕДИЧНОЇ РЕФОРМИ В УКРАЇНІ (Світ фінансів, 2019)
Кнейслер О. В., Шупа Л. З. Вектор розвитку медичного страхування у контексті сучасної медичної реформи в Україні.Окреслено положення медичної реформи, які порушують конституційні права українців на безкоштовну медицину. Зроблено висновки про позитивні перспективи запровадженої медичної реформи. Зазначено негативну тенденцію контрактної моделі охорони здоров’я. Проаналізовано запропоновану модель системи охорони здоров’я в Україні. Запропоновано прийняття Закону України “Про загальнообов’язкове медичне страхування”. Кнейслер О. В., Шупа Л. З. Вектор развития медицинского страхования в контексте современной медицинской реформы в Украине.Очерчено положения медицинской реформы, нарушающие конституционные права украинцев на бесплатную медицину. Сделаны выводы о позитивных перспективах внедренной медицинской реформы. Отмечена негативная тенденция контрактной модели здравоохранения. Проанализирована предложенная модель системы здравоохранения в Украине. Предложено принятие Закона Украины “Об общеобязательном медицинском страховании”. Kneysler О., Shupa L. Vector for the development of medical insurance in the context of modern medical reform in Ukraine.Introduction. The current practice of functioning of the medical sector shows the existence of problems that impede the introduction of compulsory health insurance in Ukraine, the effective development of its voluntary form. At the same time, the problems of development of medical insurance under the influence of crisis phenomena of the national economy are deepening.The purpose of the article is to develop recommendations for improving medical reform in Ukraine.Results. The most controversial moment in the reform of health care was the rejection of free medicine, the right to which is enshrined in the Constitution of Ukraine. However, budget medicine in Ukraine will still remain, however, in what volumes and at what stages of provision of medical services or medical care is not yet defined in the Ministry of Health of Ukraine. The negative trend of the contracted health model is the creation of an authorized body that will not only implement health policy but, in fact, formulate this policy: to define state guarantees, needs for medical services and to check the quality of these services. And this is a huge threat, because Ukrainian medicine will be in a worse situation than it is now. We believe that the policy-making function should remain under the Ministry of Health of Ukraine. The negative aspect of modern medical reform in Ukraine is the lack of requirements for the formation of medical treatment protocols. This can be explained by the fact that patients will continue to prescribe treatment that is untrue. Instead, for the health insurance, the insurance company would monitor costs and control the appointment of treatment for the patient, the price of medical services. In this context, we propose to adopt the Law of Ukraine “On Compulsory Health Insurance”, which stipulates and clearly defines the rights and obligations of the insurer, the insurer, the list of services, their price, a single register of insured persons, the formation of the Social Health Insurance Fund and a differentiated approach to categories of the population.Conclusions. The experience of developed countries of the world proves that achieving this goal is possible through the introduction of insurance medicine. Insurance medicine is a real alternative to budget financing, which is no longer capable of ensuring the constitutional right of citizens to receive unpaid health care. The development of health insurance is an objective need, which is dictated by the need to ensure that healthcare receives funds. At the moment, the study of the question of the necessity of introducing compulsory health insurance is probably very relevant to all. Successful market reforms in Ukraine are impossible without the formation of an effectively organized health insurance market that can guarantee the preservation and strengthening of human health, improving the quality of medical services and the level of human life.